SISTEM PENGHARGAAN SEBAGAI VARIABEL MODERATING DALAM HUBUNGAN ANTARA GAYA KEPEMIMPINAN DAN KINERJA MANAJERIAL (STUDI PADA SUPERMARKET DI KOTA MATARAM) - SRI AYU FEBRIANTI; I GUSTI AYU OKA NETRAWATI; I GUSTI PUTU BAGUS SUASTINA (Universitas Mahasaraswati Mataram, 2021)
The aim of this study is to analyzed the influence of leadership style on managerial performance and the reward system as the moderating variable that may affect the relationship of leadership style on managerial performance. The type of this research is associative. Respondents are managers and staff with the lowest level of supervisor in the entire supermarket in Mataram, as many as 66 respondents. Sampling technique is census. Using simple regression analysis and Moderated Regression Analysis (MRA) as analysis. The results showed that leadership style negative significantly influence on managerial performance and the reward system influence negatively significant the relationship of leadership style on managerial performance.